EKSISTENSI DAN PENGEMBANGAN KERAJINAN ANYAMAN ANGGREK (SORUME) DI KABUPATEN KONAWE - Sarman Sarman (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2026)
This study examines the sustainability of sorume-based weaving craftsmanship among the Tolaki community in Konawe Regency, Southeast Sulawesi, and explores the socio-cultural dynamics affecting its continuity. A descriptive qualitative approach was employed using observation, in-depth interviews, and documentation. Informants included weaving artisans, traditional leaders, and community members involved in the use and distribution of sorume raw materials. The findings show that sorume weaving functions not only as a traditional handicraft but also as a marker of cultural identity and social symbolism within Tolaki society. Sorume, the primary raw material, is historically found in Mowewe, East Kolaka Regency, creating a dependency of Konawe artisans on supply networks from that area. Historically, sorume weaving was associated with the prestige of the aristocratic class (sangia), but it has gradually transformed into a cultural commodity accessible to a broader public. The study further reveals that weaving skills are transmitted through women within the domestic sphere; however, artisan regeneration faces challenges due to declining youth interest, the complexity of production processes, and limited raw material availability. From Pierre Bourdieu’s perspective, this situation reflects a weakening transmission of cultural capital within artisan families. At the same time, cultural commodification creates a tension between cultural preservation and market demands. Although commodification has altered the symbolic meaning of sorume, it has also contributed to maintaining the continuity of the weaving tradition amid contemporary social change.